Produção editorial em educação midiática: Pare e Pense - projeto de combate à desinformação para jovens santamarienses - Santos, Júlia Bortolin dos (2023)
The Stop and Think Project consists of creating a booklet to combat disinformation for 2nd year high school students from two public schools in Santa Maria - RS, as an experimental project for completing the Editorial Production course at the Federal University of Santa Maria (UFSM). From the objective of serving as support material in the exercise of Media Education within the school environment, and in accordance with the provisions of the National Common Curricular Base (BNCC), it aims to develop with students a dialogue on recognizing and combating disinformation in the digital space, identifying their prior knowledge and also the needs of the school community in Santa Maria concerning the access and consumption of information, thinking about actions from what was observed. Based on a questionnaire applied to the students, the responses collected guided the creation of a printed booklet on disinformation, which was tested by participants during workshops held in the final phase of the project.